Antiangiogenic Agents for Nonmalignant Brain Tumors - Hawasli, Ammar H.; Rubin, Joshua B.; Tran, David D.; Adkins, Douglas R.; Waheed, Shahid; Hullar, Timothy E.; Gutmann, David H.; Evans, John; Leonard, Jeffrey R.; Zipfel, Gregory J.; Chicoine, Michael R. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective To assess the treatment response and side effects for the use of antiangiogenic agents such as vascular endothelial growth factor (VEGF) inhibitors for patients with vestibular schwannomas and meningiomas.Design and Methods Retrospective review of eight male and two female patients (ages 14 to 70, mean 36 years), treated with bevacizumab (9) or pazopanib (1). Six patients had neurofibromatosis type 2 (NF2) with bilateral vestibular schwannomas and meningiomas, and the four others had aggressive recurrent meningiomas.Results During treatment (range 4 to 21 months, mean 9.1) with antiangiogenic agents, two patients with an atypical meningioma and radiation necrosis had dramatic partial response, the six NF2 patients had stable or slightly improved disease, and two meningioma patients had disease progression. Hearing was stable in three of the NF2 patients and was improved in three NF2 patients (one of whom received a cochlear implant). Minor toxicities included epistaxis, nausea, diarrhea, weight loss, and abdominal pain. No grade 3 or 4 toxicities were observed.Conclusion Antiangiogenic agents appear to be safe for the treatment of patients with nonmalignant brain tumors, and in select cases may be efficacious.
Keywords: brain tumor; meningioma; vestibular schwannoma; vascular endothelial growth factor; neurofibromatosis; bevacizumab; pazopanib